Investigation of the dynamical behavior of the Hirota-Maccari system in single-mode fibers - Tarla, Sibel; Ali, Karmina K.; Yilmazer, Resat; Yusuf, Abdullahi (Springer, 2022)
In this paper, we use the Jacobi elliptic function expansion approach to investigate the Hirota-Maccari system which describes the dynamical behaviors of the femto-second soliton pulse in single-mode fibers. As a result, solutions with various structures are developed including dark-bright, dark, single, brilliant, exponential function, and Jacobi elliptic function solutions. In addition, a computer application is used to examine the solutions found on three-dimensional surfaces and two-dimensional visuals.
Keywords: Solitary solutions; Nonlinear Hirota-Maccari system; Jacobi elliptic function expansion method; Exact solutions